1939
DOI: 10.1002/zaac.19392410208
|View full text |Cite
|
Sign up to set email alerts
|

Über den thermischen Zerfall der Ammoniumchromate

Abstract: Beim Zerfall der Ammoniumchromate verarmt die Oberfläche wahrend der Einstellperiode an Ammoniak. Dieser Vorgang führt nicht zu einer Übersättigung, die den weiteren Ablauf des Zerfalls hemmen wurde, da ja kein Gleichgewicht zwischen den Reaktionsprodukten und dem Ausgangsmaterial besteht. In der aufgelockerten Oberfläche tritt die Oxydation der Kationen durch die Anionen ein, und diese Reaktion pflanzt sich nach einem einfachen Zeitgesetz durch den Rest des Kristalls fort. Dabei hat sich herausgestellt, daß d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1953
1953
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For instance, early investigations [25,26] claimed the formation of CrO3 as a consequence of the elimination of NH3, by a proton transfer-type mechanism, followed by H20 molecules. Recent mass-spectrometric gas analysis results [17], however, have indicated that at this stage (200 ~ the evolved gases consist of about 52% NzO, 21% N2, 26% H20 and free NH3 of less than 1%.…”
Section: Thermal Analysis Of Ammonium Dichromate (Adc)mentioning
confidence: 99%
“…For instance, early investigations [25,26] claimed the formation of CrO3 as a consequence of the elimination of NH3, by a proton transfer-type mechanism, followed by H20 molecules. Recent mass-spectrometric gas analysis results [17], however, have indicated that at this stage (200 ~ the evolved gases consist of about 52% NzO, 21% N2, 26% H20 and free NH3 of less than 1%.…”
Section: Thermal Analysis Of Ammonium Dichromate (Adc)mentioning
confidence: 99%
“…The photochlorination of methyl chloroformate has been studied in the gas phase and the results compared with those obtained for the reaction in carbon tetrachloride solution. 117 Other Direct Photochemical Reactions.--A detailed investigation has been made of the photochemical and thermal decomposition of hydrogen sulphide in the range 27-650"/8--550 mm. and at wave-lengths 2288 A and 2550 A,11s the decomposition of hydrogen bromide being used as actinometer at 2288 A.…”
Section: Thermochemistrymentioning
confidence: 99%